The Relationship Of Interest In Reading To The Comprehension Reading Ability Of Grade V Students In Elementary School : Hubungan Minat Membaca Terhadap Kemampuan Membaca Pemahaman Siswa Kelas V Di Sekolah Dasar - Mufidah , Nurul Lailatul; Wachidah, Kemil (Indonesian Journal of Education Methods Development, 2023)
This study investigates the association between reading interest and reading comprehension ability among fifth-grade students at BalongGabus Candi State Elementary School. Employing a quantitative correlational approach, data collection involved questionnaires and comprehension tests for 23 students. The computed correlation coefficient (r = 0.756) demonstrated a robust relationship between the two variables, signifying a 57.15% connection strength. This significant finding suggests that reading interest greatly influences reading comprehension prowess in this cohort. Highlights: Strong Correlation: A robust correlation coefficient (r = 0.756) highlights a substantial and positive relationship between reading interest and reading comprehension ability among fifth-grade students. Influential Factors: The study underscores the significance of reading interest as a determining factor in enhancing reading comprehension skills among young learners. Quantitative Insights: Employing a quantitative approach with a sample of 23 fifth graders, this research provides valuable insights into the interplay between reading engagement and comprehension proficiency. Keywords:Reading interest, Reading comprehension, Fifth graders, Correlation, Quantitative approach